2005
DOI: 10.1038/nature03493
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular APOBEC3G restricts HIV-1 infection in resting CD4+ T cells

Abstract: In contrast to activated CD4+ T cells, resting human CD4+ T cells circulating in blood are highly resistant to infection with human immunodeficiency virus (HIV). Whether the inability of HIV to infect these resting CD4+ T cells is due to the lack of a key factor, or alternatively reflects the presence of an efficient mechanism for defence against HIV, is not clear. Here we show that the anti-retroviral deoxycytidine deaminase APOBEC3G strongly protects unstimulated peripheral blood CD4+ T cells against HIV-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
477
3
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 406 publications
(518 citation statements)
references
References 30 publications
37
477
3
1
Order By: Relevance
“…The GFP-labeled virions infecting CCR5 ϩ HEK 293 cells are independent of CD4 and CCR5 expression due to the presence of a VSV envelope, so inhibition of the viral infection is most likely to be due to the intracellular A3G generated by stimulation with HSP70. Furthermore, the pseudo virus features only a single round of infection, which suggests that the A3G-inhibitory effect occurs during the early stages of infection, as observed recently with the low molecular mass (LMM) form of A3G (8). Interestingly, there is evidence that LMM A3G may be resistant to the actions of Vif, FIGURE 5.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The GFP-labeled virions infecting CCR5 ϩ HEK 293 cells are independent of CD4 and CCR5 expression due to the presence of a VSV envelope, so inhibition of the viral infection is most likely to be due to the intracellular A3G generated by stimulation with HSP70. Furthermore, the pseudo virus features only a single round of infection, which suggests that the A3G-inhibitory effect occurs during the early stages of infection, as observed recently with the low molecular mass (LMM) form of A3G (8). Interestingly, there is evidence that LMM A3G may be resistant to the actions of Vif, FIGURE 5.…”
Section: Discussionmentioning
confidence: 66%
“…thus making it more desirable as an anti-HIV agent than its nonVif-resistant high molecular mass A3G counterpart (8). Whether HSP70 up-regulates only the LMM or both forms of A3G requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] Recent evidence suggests that some of the HIV restriction exerted by A3G may be independent of its cytidine deaminase activity. [24][25][26] G-to-A hypermutated HBV genomes have been detected in the plasma of HBV-infected patients, suggesting that APOBEC3 editing enzymes have edited the minus strand cDNA during HBV replication. [27][28][29] In hepatoma cells, transfection of A3B, A3C, A3F, or A3G induced extensive hypermutations in a minor fraction (approximately 10 Ϫ3 ) of HBV genomes that was detected by a novel polymerase chain reaction technique (3D-PCR) designed to selectively amplify AT-hypermutated sequences.…”
mentioning
confidence: 99%
“…Recently it was demonstrated that intracellular apolipoprotein B mRNA-editing enzyme, catalytic polypeptide-like 3G (APOBEC3G) has a role in blocking HIV-1 replication in quiescent CD4 ϩ T cells and monocytes (24). In activated CD4 ϩ T cells and monocyte-derived macrophages APOBEC3G is present as a high molecular mass (HMM) inactive ribonucleoprotein complex that correlates with these cells being permissive for HIV-1 replication.…”
mentioning
confidence: 99%